Experimental Investigation of Unsaturated Silt-Sand Soil Permeability - Samad Nazari; Mahmoud Hassanlourad; Elham Chavoshi; Ali Mirzaii (Advances in Civil Engineering)
The permeability of unsaturated silt-sand soil is important in many geotechnical and geoenvironmental challenges. Therefore, an appropriate method to evaluate silt-sand soil permeability is important, particularly in Iran where it received little consideration. In this in vitro research, different amounts of fine silt were evaluated on behavior of an unsaturated silt-sand soil with different grain size distribution using a new modified triaxial apparatus. Permeability was measured against matric suction and volumetric water content, and the results are compared against experimental models. The results indicated that the behavior of unsaturated sandy soil permeability could be determined as a function of matric suction, soil void size, and percentage of fine aggregate. Furthermore, the results appeared to imply that an increase of fine contents reduced the permeability, specifically at higher values of suction. This trend for the reduction of soil permeability was related to the increase in the amount of fine contents.